Analysis Impact Test and Hardness Test on Construction Steel with Quenching Oil SAE 40 Cooling Media at Heat Treatment Temperature Variation 700, 800 and 900 ºC - Sri Mulyo Bondan Respati; Mujiyono Mujiyono; Helmy Purwanto (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Research on the market construction steel was heat treatment with oil quenching has been done.The purpose of this experiment to increase the strength of the steel construction.The method was started from the construction steel, heated at a temperature of 700, 800, 900 °C with a holding time of 60 minutes and then cooled rapidly using SAE 40 oil medium at room temperature.Results achieved higher heating temperature the increase the hardness, but the toughness decrease.This shows that the quenching treatment with oil medium will increase the hardness and create brittle.Keywords: Heat treatment, Hardening, Holding Time, Quenching.